Barnyard grass (Echinochloa crus-galli L.) as a candidate plant for phytoremediation of arsenic from arsenic-amended and industrially polluted soils - Sultana, Razia; Ahmed, Tamim; Islam, Shah Mohammad Naimul; Uddin, Md Nizam (Frontiers in Soil Science, 2022)
The potentiality of barnyard grass for remediation of arsenic (As) contaminated soil has been reported in several research works. However, the phytoremediation ability of barnyard grass from industrially polluted multimetal contaminated soil in comparison to As amended soil needs to be elucidated. This work investigated the As remediation potentiality of barnyard grass from As amended and industrially polluted soils and the fractionation of As was done in soils with plant and without plant grown. The result showed that, at the highest soil As level, the barnyard grass accumulated the highest amount of As in both root (414.81 mgkg-1) and shoot (114.12 mgkg-1). However, the barnyard grass produced the highest amount of biomass in industrially polluted soil resulted in the highest amount of As uptake. Moreover, barnyard grass also accumulated Pb and Cr from industrially polluted soil. The bioaccumulation factor of As was more than one (1) in As amended soil in all the treatments as well as in industrially polluted soil. Fractionation of post-harvest soil As revealed that compared to soil without plant grown, soil As reduced from residual As (F5); As associated with well crystallized hydrous oxides of Fe and Al (F4); As associated with amorphous and poorly-crystalline hydrous oxides of Fe and Al (F3), whereas, a slight increase was found in non-specifically sorbed As (F1) and specifically sorbed As (F2) due to the plant’s effect. The slight increase in concentration of As in F1 and F2 fractions contributed to the bioavailable forms of As in the rhizosphere and sustained the As concentration for further plant uptake. The maximum plant growth and highest uptake of As in the industrially polluted soil revealed the potentiality of barnyard grass for remediation of multimetal polluted soil.